The Policy Suggestions Concerning Motivations and Barriers of University-Industry Cooperation - Seppo, Marge; Roolaht, Tõnu (Estonian Discussions on Economic Policy, 2012)
The universities as scientific and educational bodies transform into entrepreneurial organizations focusing on cooperation with industry. The motivations for increased cooperation with industry include additional funding of research, application of research results in practice, sharing experiences with practitioners, discovering novel research problems, and securing jobs for alumni. Industries seek cooperation with universities in order to build competitive advantage, increase productivity, gain access to new technologies and to potential qualified labour, influence curricula development, use labs and equipment, and to improve image. The barriers to cooperation include differences in goals and culture, miscomprehensions, biased attitudes, remuneration systems, different focuses, lacking communication, and difficulties in commercialization. The purpose of this study is to suggest policies to enhance motivations and/or reduce barriers of university-industry cooperation.